RMK 353 - Property Management - December 2013 / January 2014 - PPPBP, Pusat Pengajian Perumahan Bangunan Dan Perancangan (2013)
First Semester Examination Academic Session 2013/2014 December 2013 / January 2014 Duration : 3 hours